Influence of occlusal loading on the longevity of dental bridges - Aqely, Mona A.; Faraj, Mayyada I.; Alnafisi, Aasaiel A.; Ayoub, Mohammed N.; Diqini, Ibrahim M.; Majrashi, Nawal M.; Alajam, Ismail A.; Alsheri, Aisha M.; Alrayes, Nouf A.; Alahmari, Haitham A.; Alghabban, Abdulmohsen S. (International Journal Of Community Medicine And Public Health, 2025)
Dental bridges are a cornerstone in restorative dentistry, offering functional and aesthetic solutions for patients with missing teeth. Their longevity is influenced by a complex interplay of biomechanical, material, and clinical factors. Occlusal loading, the force exerted during mastication and other functional activities, plays a critical role in determining the durability of these prostheses. Excessive or uneven occlusal forces can lead to mechanical failures such as fractures, debonding, or material fatigue. Advances in materials, particularly high-strength ceramics like zirconia, have improved the ability of bridges to withstand these stresses, providing enhanced resistance to wear and fracture. Design considerations, including connector dimensions and the use of computer-aided design and computer-aided manufacturing (CAD/CAM) technology, ensure more precise stress distribution, minimizing the risk of localized mechanical failures. Finite element analysis and digital occlusal analysis have further refined the understanding of stress patterns, enabling personalized approaches tailored to individual patient needs. Clinical studies have highlighted the importance of maintenance strategies, such as regular follow-ups and early repair of minor defects, in extending the lifespan of dental bridges. Patient-specific factors, such as parafunctional habits and periodontal health, significantly influence outcomes and necessitate individualized treatment planning. Emerging technologies, combined with material innovations, have shifted the focus toward optimizing the biomechanical performance of dental bridges. Trends reveal that integrating robust materials with advanced design techniques results in improved longevity and reduced failure rates. The interplay between clinical, material, and mechanical factors continues to evolve, offering new insights into enhancing the reliability and success of dental bridges over time.